Blend of multi-walled carbon nanotubes and quercetin improves physicochemical properties of chitosan membrane for wound dressing application - Baktehir, Nurul Huda (Penerbit UTM Press, 2023)
Although wound dressings are essential to protect wound from infection, these wound care products have limited function in facilitating wound healing. This study aimed to synthesize multi-walled carbon nanotube (MWCNT)/quercetin (QUE)/chitosan (CS) blended composite membrane and analyze their physicochemical properties for wound dressing application in comparison to the pure chitosan (CS) membrane. The MWCNT/QUE/CS blended membranes were prepared by mixing CS, QUE and MWCNT at a ratio of 3:1:1 using a solvent casting method. The membranes were analyzed physicochemically for their surface morphology, elemental composition, structural composition, wettability, water vapor transmission rate (WVTR) and swelling properties and were compared to the pure CS membrane. The findings pointed out that the blend of MWCNTs and QUE in the CS matrix produces a membrane with uneven and more hydrophilic surface with water contact angle of 64.70°± 3.7 and low WVTR of 16.26 g/m2.day after 24 h. The swelling analysis showed that the blended membrane was able to absorb more than 60% of water within 10 minutes, although lower than the pure CS membrane. This study revealed that MWCNT/QUE/CS blended membrane could possibly be used as a wound dressing as it may promote moist environment needed for wound healing in addition to its antibacterial and antioxidant properties that may accelerate wound healing process.